2021
DOI: 10.3390/en14030636
|View full text |Cite
|
Sign up to set email alerts
|

The Road to Developing Economically Feasible Plans for Green, Comfortable and Energy Efficient Buildings

Abstract: Owing to the current challenges in energy and environmental crises, improving buildings, as one of the biggest concerns and contributors to these issues, is increasingly receiving attention from the world. Due to a variety of choices and situations for improving buildings, it is important to review the building performance optimization studies to find the proper solution. In this paper, these studies are reviewed by analyzing all the different key parameters involved in the optimization process, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…With today's needs for energy savings and control of the building's environmental impacts [1,2], some doubts arise about the definition of thermal comfort and how to create and maintain comfort conditions as they are dependent on geographical location of building [3], as such person-to-person perceptions changes, and the type of activities performed. In situ studies of thermal comfort have revealed an overestimation of the level of perceived discomfort in reality compared to that predicted by regional building standards, especially in buildings that are air-conditioned during hot periods [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With today's needs for energy savings and control of the building's environmental impacts [1,2], some doubts arise about the definition of thermal comfort and how to create and maintain comfort conditions as they are dependent on geographical location of building [3], as such person-to-person perceptions changes, and the type of activities performed. In situ studies of thermal comfort have revealed an overestimation of the level of perceived discomfort in reality compared to that predicted by regional building standards, especially in buildings that are air-conditioned during hot periods [4].…”
Section: Introductionmentioning
confidence: 99%
“…The development of thermal comfort techniques has played a paramount role to enlighten comfort parameters with various renewable energy technologies [17][18][19]. This epoch is characterized by the progress and enhancement of thermal machines [2]. It is imperative to mention that thermal comfort is also dependent on stress-free satisfaction of energy consumption, as such low-energy power generation [20,21] with PV integrated solar thermal systems [22][23][24], advanced smart building wall insulation technologies and smart windows [25,26] are growing in remote regions of the countries, where access to electric grid [27] is still under-development, and in fact a successful notion of smart cities with advanced insulation technologies where individual buildings could be self-energy reliant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinez, Duarte [17] speaks about improving the environmental quality in educational buildings, Tsala and Koronaki [18] talk about strategies of saving energy in a campus building in Athene, while Erebor, Ibem [19] takes into account the application on the energy efficiency in office buildings. Mousavi Motlagh, Sohani [20] present, in a valuable review of research, a wide review on economically feasible plans for green, comfortable, and energy-efficient buildings, touching directly on the principals of the bioclimatic architecture, where the author collects several recent works on the bounding optimization field treating several building types as well as community centers, tourist center, rest areas, university, museums, and much more. Furthermore, based on a strong review, the author divided the building optimization process into two main categories: the single-objective optimization (SOO) and multi-objective optimization (MOO).…”
Section: Introductionmentioning
confidence: 99%
“…position, external shading, and glazing properties Al-Saggaf et al [ In a building, several aspects are involved, and researchers investigate a building from different perspectives. Each of these aspects can be then evaluated by some quantitative indicators that have been considered as the objective functions in the literature [21]. In order to investigate these objectives in a building, depending on the considered objectives, researchers usually use a variety of building simulation software programs, such as EnegyPlus (funded by the U.S. Department of Energy (DOE)), DesignBuilder (Stroud, Gloucestershire, UK), Radiance (developed by Greg Ward, Berkeley, CA, USA) etc.…”
Section: Introductionmentioning
confidence: 99%